2020
DOI: 10.1364/ol.387669
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for terahertz emission of continuum electrons in the dual-color laser field

Abstract: Terahertz (THz) wave generation (TWG) in a dual-color laser is investigated with joint measurements between THz and third-harmonic generation, where the relative phase delay of dual-color fields is determined in situ in sub-wavelength accuracy, allowing for the clarification of the TWG mechanism in a direct comparison with various theoretical predictions. The delay- and polarization-dependent experiment validates that the continuum–continuum transition within the escaped electron wavepacket in the single atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…Compared against the photocurrent model from macroscopic viewpoint, the strong-field approximation (SFA) is a successful workhorse of strong-field physics under quantum mechanical treatment. The continuum-continuum transition in the SFA dipole moment [14] has precisely reproduced the phase-and polarization-dependent measurement of TWGs [15,16], proving the feasibility of SFA theory. The semiclassical method of SFA theory, where the electron tunnelling is treated quantum mechanically and its subsequent motion is envisioned as classical Newtonian particle trajectory, can connect the TWGs and photoelectron momentum distributions (PEMDs) [17][18][19][20], providing new insight into the microscopic mechanism of TWG.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Compared against the photocurrent model from macroscopic viewpoint, the strong-field approximation (SFA) is a successful workhorse of strong-field physics under quantum mechanical treatment. The continuum-continuum transition in the SFA dipole moment [14] has precisely reproduced the phase-and polarization-dependent measurement of TWGs [15,16], proving the feasibility of SFA theory. The semiclassical method of SFA theory, where the electron tunnelling is treated quantum mechanically and its subsequent motion is envisioned as classical Newtonian particle trajectory, can connect the TWGs and photoelectron momentum distributions (PEMDs) [17][18][19][20], providing new insight into the microscopic mechanism of TWG.…”
Section: Introductionmentioning
confidence: 56%
“…The trajectory method derived from SFA in the semiclassical limit is introduced to explain the TWG. Since the contributions of the rescattering electron have been excluded [15], only the 'direct' electron is taken into account. The bound electron is released at the ionization instant t i and subsequently driven only by the strong laser field without interaction with its parent ion.…”
Section: Methodsmentioning
confidence: 99%
“…The laser induced gas plasma involves rather complicated processes dominated by the strong field photoionization. In this sense, the two-color field induced THz wave generation (TWG) has been interpretated under the framework of strong field theory as the continuum-continuum transition [17][18][19], complementary to the continuum-bound transition mechanism for highorder harmonic generation (HHG) [20], i.e., the emssion of high energy photon when the released electron recollides with the parent ion after the ionization.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, much effort has been made to explain the TWG within the strong-field theoretical framework, including the strong-field approximation (SFA) model [13] and numerical solving time-dependent Schrödinger equation [14]. Recently, our experimental and theoretical works indicated that the TWG originates from the continuum electron under single active electron approximation, and established the link between quantum mechanical SFA and classical PC models [15,16]. However, which kind of electron behaviors in convoluted tunneling dynamics produces the TWG still remains indistinct.…”
mentioning
confidence: 99%
“…The S 3ω (τ ), shown in Fig. 2(a2), are jointly measured with S THz (τ ) for experimentally in situ calibration of the phase delay τ [15]. The experimental detail is referred in Supplemental Material S. .…”
mentioning
confidence: 99%